The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/1814082
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Method for Modeling the Peculiar Dynamics of Transient Carbon Plasma Generated by Excimer Laser Ablation in Vacuum

Abstract: Carbon plasmas generated by excimer laser ablation are often applied for deposition (in vacuum or under controlled atmosphere) of high-technological interest nanostructures and thin films. For specific excimer irradiation conditions, these transient plasmas can exhibit peculiar behaviors when probed by fast time- and space-resolved optical and electrical methods. We propose here a fractal approach to simulate this peculiar dynamics. In our model, the complexity of the interactions between the transient plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, the extremely condition in tokamak like vacuum, strong magnetic field, discharge plasma background made the LIBS quantitative analysis further complicated. The basic processes of nanosecond laser ablation with subsequent plasma formation and expansion have been investigated in depth in recent years using theoretical simulations [15][16][17][18][19][20][21][22] and experimental methods [23][24][25][26][27], which also have been summarized in detail in numerous investigations and books [9,26,[28][29][30][31][32]. Nevertheless, the long-time scale and space dependent properties make the full description of laser ablation and plasma formation still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the extremely condition in tokamak like vacuum, strong magnetic field, discharge plasma background made the LIBS quantitative analysis further complicated. The basic processes of nanosecond laser ablation with subsequent plasma formation and expansion have been investigated in depth in recent years using theoretical simulations [15][16][17][18][19][20][21][22] and experimental methods [23][24][25][26][27], which also have been summarized in detail in numerous investigations and books [9,26,[28][29][30][31][32]. Nevertheless, the long-time scale and space dependent properties make the full description of laser ablation and plasma formation still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma formation and the associated dynamical processes are results of transitions from various ordered and disordered states. Thus the laser-plasma ablation can be treated as a complex selfsimilar chaotic process that occurs in space-time scales [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The greater spatial and temporal resolution and no sample preparation difficulty enable the study of complex combustion and aerodynamical processes employing LIBS that are described based on inverse Bremsstrahlung and multi-photon absorption [29]. When the studies by Chen et al [33] reported the significance of using spatial and temporal resolution techniques to analyse the stochastic process associated with the laser-induced breakdown, Ursu et al [21] introduced a fractal model to explain the complexity of the transient plasma particle interaction in a fractal space and Viana et al [34] explained the role of the fractal structures in analysing electromagnetic turbulence in plasmas. The present work is a novel and simple approach to analyse the plasma dynamics through power spectral fractal analysis of the plasma emission spectrum, taking copper plasma as an example.…”
Section: Introductionmentioning
confidence: 99%
“…The basic nanosecond laser-ablation processes, including plasma formation and expansion, have been thoroughly investigated using theoretical [1][2][3][4][5][6][7][8] and experimental methods [9][10][11][12] over the last two decades. During the plasma formation process, electrons, ions, and atoms in the plasma expand away from the ablation surface, producing strong optical emission, including continuum radiation and line emission.…”
Section: Introductionmentioning
confidence: 99%